Analysis of Key Environmental Impact Factors Based on Fuzzy Clustering and Grey T' s Correlation Degree Method. (February 2019) - Zhao, Gaofei; Huo, Yujie; Zhang, Zhaofeng; Peng, Zhaoyuan
Abstract: This paper expounds the basic principle of fuzzy clustering and grey T' s correlation degree method. It takes a power module used in communication device and worked outfield as an example to analysis the impacts of natural environment factors on product, that based on failure rate. Firstly, fuzzy clustering method is used to classify the environmental factors into four categories. Secondly, grey T' s correlation degree method is used to compare and rank the degree of influence of the four types of factors on the failure rate of power module. Finally, the analysis method and the key environmental factors affect the failure of the power module are given. The analysis of key influencing factors lays a foundation for the analysis of failure causes and mechanism of products, and provides a basis for reliability test design.